The Role of Women in Reducing Radicalism Through Nahdlatul Ulama Organization - Mustaniroh Mustaniroh; Muhamad Ibnu Soleh Al Mubarok; Ahmad Musadad; Galuh Widitya Qomaro; Tri Pujiati (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
The phenomena of radicalism considered as a trigger disturbing terrorism​ security and peace in Indonesia. History recorded that before 2016, women become passive perpetrator in terrorism. However, after 2016 until present, the women become active with amount participation increase sharply. Terrorist figures often want to carry out Islamic law with perfect so that often connected with method drastic violence, such as bomb kill themselves. This research has an effort to see the role of woman in activity of radicalism in Indonesia. This research has an objective to describe efforts made​ NU Muslim women in deradicalization radicalism in Indonesia. This research uses descriptive qualitative approach by using library research technique. The result of this study shows that Muslimat NU as one of the organization social religious the largest in Indonesia has role important for minimize hostility that occurred. Moreover, this study found that Muslimat NU uses approach education, culture, structural, and economic. Implementation from study show that the approach taken by NU Muslim women are able to strengthen unity in reducing radicalism in Indonesia.